Study of Operational Strategies and Carbon Source Selection for the Production of Phytase using Pichia pastoris - Zhong, Shuping (Université d'Ottawa / University of Ottawa, 2015)
The methylotrophic yeast Pichia pastoris has become an efficient expression system for heterologous protein production. Different methods have been studied to enhance cell growth as well as the production of products of interest. Two of the major strategies for improving the product or biomass yields are optimizing bioprocess controls and cultivation conditions. In this work, the characteristics of this yeast system and of its different promoters are discussed, and the effect of operational strategies on cell growth and recombinant protein expression is also studied. The effect of different feeding strategies were studied and optimized for pGAP (glyceraldehyde-3-phosphate dehydrogenase)-regulated phytase production in P. pastoris. Alternative carbon sources were screened and the feasibility of using citric acid as a carbon source for recombinant protein production was also investigated. The effects of parameters such as the carbon source concentration and culture pH were studied using shake-flasks, and the effect of different feeding profiles on bioreactor performance was also investigated. Three feeding strategies, Stepwise feeding, Exponential feeding and DO-stat feeding were tested and DO-stat was found to be more efficient and led to a high phytase activity. A modified DO-stat method was investigated to overcome the oxygen limited condition in the standard DO-stat method. For the carbon source, citric acid showed promise in improving phytase expression. Further experiments in bioreactors performed with the presence of certain amount of citric acid showed that less glycerol could be used to achieve the same level of phytase activity.
Keywords: Pichia pastoris; Yeast; Carbon source; Citric acid; Fermentation; Feeding strategy